THE INFLUENCE OF WEBSITE QUALITY ON CONSUMER LOYALTY WITH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE IN E-COMMERCE LAZADA IN BANDUNG CITY - Fahira Nur Pratiwi; Mamun Sutisna (Universitas Diponegoro, 2025)
E-commerce competition in Indonesia is currently increasing. To improve their position, business actors are required to improve service quality so that consumers remain satisfied and loyal. One of the things from e-commerce that has problems and needs attention is website quality. The purpose of this study is to determine the effect of website quality on consumer loyalty with consumer satisfaction as an intervening variable in Lazada e-commerce in Bandung city. The method in this study is an explanatory survey, descriptive statistical analysis, and Structural Equation Model-Partial Least Square (SEM-PLS) data analysis using the SmartPLS 4.0 application with a sample of 131 respondents from people in Bandung city who have made purchases through Lazada website at least twice. The result show that website quality has a positive and significant effect on consumer satisfaction. Website quality has a positive and significant effect on consumer loyalty. Consumer satisfaction has no effect on consumer loyalty. Consumer satisfaction does not mediate the effect of website quality on consumer loyalty.